Karakteristik Fisikokimia Stik Jagung Dengan Subsitusi Tepung Mocaf - Nur Rohmah A'yuni; Sevi Melati; Junianto Junianto (Universitas Tidar, 2026)
Corn sticks are value-added corn products that can be manufactured using readily available ingredients and simple processing equipment. They are generally produced using wheat flour, although Indonesia remains dependent on imported wheat. Modified cassava flour (Mocaf) is a potential local ingredient that can partially replace wheat flour. This study aimed to evaluate the effects of mocaf substitution on the physicochemical properties of corn sticks. A completely randomized design with one factor, namely the proportion of mocaf and wheat flour, was applied. Three formulations were evaluated: F1 containing wheat flour only, F2 containing mocaf and wheat flour at a ratio of 1:1, and F3 at a ratio of 1:2. Increasing the proportion of mocaf tended to increase fat content, energy value, and oil absorption capacity, while decreasing protein content.